Assessment and Management of Patients with Obesity and Hypertension in European Society of Hypertension Excellence Centres. A survey from the ESH Working Group on Diabetes and Metabolic Risk Factors. - Christina Antza; Guido Grassi; Thomas Weber; Alexandre Persu; Jens Jordan; Peter M Nilsson; Josep Redon; Stella Stabouli; Reinhold Kreutz; Vasilios Kotsis (Blood Pressure, 2024)
Background Healthcare providers are faced with an increasing number of patients with obesity and arterial hypertension. Preventing obesity-associated hypertension and appropriately managing patients with established disease are both important. Hence, the aim of our study was to evaluate the clinical care of patients with obesity and hypertension among ESH Excellence Centres (ECs).Methods We conducted a cross-sectional, international 30-item survey through e-mails.Results In total, 70 representatives of ECs participated (78% men) with 66% of them practicing medicine for more than 30 years and working in well-equipped clinics. Most were internists (41%) and cardiologists (37%) and 73% reported training on the management of obese patients with hypertension. A majority weigh their patients (77%) and evaluate patients for sleep disorders (93%). However, only 47% spend more than 5min to advise for lifestyle modification in general, 59% for weight loss, 56% for salt intake and 64% for exercise. Finally, a minority of participants ask patients if they like their body (6%) or about previous attempts to lose weight (28%), evaluate 24h urinary sodium excretion rate (22%) and provide written (15%) or personalized (10%) dietary advices. If the patient suffers also from type 2 diabetes mellitus, 66% switch treatment to GLP1 receptor agonists and 60% to SGLT2 inhibitors.Conclusion Most clinicians in ESH ECs are well educated regarding obesity-associated hypertension, and clinics are sufficiently equipped to manage these patients, as well. However, several deficits were reported regarding efforts to address and implement obesity specific aspects and interventions to improve care in patients with obesity and hypertension.